Sufism Based Character Education: Strenghtening the National Character to Traditional Muslim Community in Madura - Siswanto, S. (ADDIN, 2020)
This article describes model of strengthening the national character values with the Sufism approach in the traditional Madurese Muslim community who has a sectarian and static mindset through the Majlis Maulid wa al-Ta’lim Riyadlul Jannah Madura activities. The strengthening of the national character is based on Islamic teachings which normatively emphasize the ritual and social dimensions. This Majlis builds religious values, love for the country, the spirit of nationality, tolerance, and social care. The pattern of strengthening with the Sufism approach is carried out through the reading of Maulid Simth ad-Durar, shalawat, and qashidah with national character values, mauizhah hasanah, and riyadlah through safari maulid in 40 nights and qiyam al-lail on the last 15 nights of Ramadan. The strengthening of the national character runs optimally influenced by the power of prayer, humility (tawadlu’) of the Majlis leaders, hospitality, and noble morals in every Majlis activities.